Phenotypic and molecular analyses of leaf rust resistance in some Iranian wheat genotypes. (1st October 2016) - Aliakbari Sadeghabad, Ali; Dadkhodaie, Ali; Heidari, Bahram; Razi, Hooman; Mostowfizadeh-Ghalamfarsa, Reza
Abstract: Host resistance is the most sustainable method of controlling leaf rust which can be achieved through exploring resistance genes by gene postulation and/or molecular markers. The experiment was conducted to postulate leaf rust resistance genes in 20 Iranian wheat cultivars using 10 Puccinia triticina pathotypes. Six sequence-tagged site and sequence-characterised amplified region markers were also used to detect the genes Lr9, Lr10, Lr19, Lr24, Lr26 and Lr37 . The genes Lr3a, Lr3Ka, Lr10, Lr15, Lr19, Lr26, Lr28, Lr30 and Lr27 + Lr31 genes were postulated to be present either singly or in combination. The cultivars Toos and Dabira were found to have no effective seedling resistance gene(s); The former was shown to carry none of the genes, while the latter carried Lr10, Lr24 and Lr37 based on molecular markers. It was not possible to postulate resistance genes in Sirvan, Backcross Roshan, Zagross and Chamran cultivars. However, molecular association indicated the presence of Lr19, Lr10 and Lr24 in Sirvan, Backcross Roshan, and Chamran, respectively while none in Zagross.